Professional autonomy of nurses, obstetricians and emergency medical workers - Bączyk-Rozwadowska, Kinga (Studia Iuridica Toruniensia, 2019)
The progress in medical sciences, improving qualifications of medical personel and a growing need for health services in the society require that the competences are to be transferred to other medical professions. Nurses, midwives and emergency medical workers, who have so far been considered as auxiliary staff, are acquiring more and more qualifications which have previously been entrusted to physicians, and they are assuming the role of partners to physicians in the field of diagnosis and therapy. The latest regulations concerning the pursuit of the profession of a nurse, midwife and emergency medical worker seem to confirm this tendency. Thus, the analysis of the new rules is essential from the point of view of preserving proper relations between doctors and other medical personnel, appropriate functioning of the health care system and the patients’ wellbeing.